Effect of Pheretima aspergillum on reducing fibrosis: A systematic review and meta-analysis - Xu, Tianren; Liu, Xiaonan; Wang, Shengguang; Kong, Hongwei; Yu, Xiaojun; Liu, Congying; Song, Huaying; Gao, Peng; Zhang, Xin (Frontiers in Pharmacology, 2022)
Background:Pheretima aspergillum (common name: Earthworm, Chinese name: dilong) has been used in traditional Chinese medicine for thousands of years. Recently, a few scientific studies have investigated the antifibrotic effects of Dilong extract (DE) and produced controversial results. We conducted a meta-analysis to make an informed decision on the antifibrotic effects of Dilong extract. Methods: The studies on antifibrotic effects of Dilong extract published until July 2022 in the scientific databases [PubMed, Web of Science, China National Knowledge Infrastructure (CNKI), VIP database for Chinese Technical Periodicals, SinoMed and WanFang database] were reviewed. The RevMan 5.4.1 software was used for standardized mean difference (SMD) analysis. Two researchers independently reviewed all the studies, and their quality was assessed using the Cochrane risk of bias tool. Results: A total of 325 studies were found in the scientific databases; however, only 13 studies met the criteria for analysis. Dilong extract treatment was associated with antifibrotic effects via inhibiting the transforming growth factor beta 1 (TGF-β1, SMD = −3.16, 95% CI: −4.18, −2.14, p < .00001) and alpha-smooth muscle actin (α-SMA: SMD = −2.57, 95% CI: −3.47, −1.66, p < .00001). Conclusion: Dilong extract effectively reduces tissue fibrosis; thus, further scientific studies should be conducted to investigate and develop it for clinical use. Systematic Review Registration:https://www.crd.york.ac.uk/prospero/, identifier CRD42022357141.